Marketing Sustainable Retail Development - Ilić, Dragan; Stanković, Jasmina (Journal of Economic Development, Environment and People, 2013)
One of the primary benefits of sustainable retail over the long run has to be the marketing gain from having something other competitors do not: lower operating costs, a more socially responsible public profile, ease of gaining planning approval for new projects, better access to certain investment pools, higher rents (in the case of developers), ease of recruiting and retaining key people. Each of these benefits needs marketing and public relations support; each benefits from a clear and consistent corporate message that promotes sustainable retail. To date, there are very few retailers or developers who have championed sustainability long enough, consistently enough and with enough actual demonstration of changes in standard operations to gain the benefits of green marketing, but the very paucity of examples serves to underscore the point: the green marketing space is wide open for large retailers and developers. What would be the marketing steps that a company could take to benefit from its “sustainability focus?” The key to any marketing program is to differentiate a company’s actions from those of competitors and to do it along lines that its various stakeholders care about. This practice of differentiation is often expressed as “finding a difference that makes a difference, to someone who makes difference to you.” For retail developers, the first differentiator should be to attract more and better tenants to all of their centers, tenants who value lower operating costs and the developer’s program of sustainable development and corporate social responsibility.